Addressing Counterfeit Medicines and Community Risk: Insights from South African Spaza Shops - Michael Mncedisi Willie; Athandile Hadebe (CV Media Inti Teknologi, 2026)
Background: Governance and regulatory enforcement in South Africa reveal complex interactions among formal legal frameworks, operational capacity, and informal market practices. While deliberative processes, such as public consultations on the draft Traditional Courts Regulations, demonstrate transparency and inclusivity, interventions in the healthcare sector are often reactive, triggered by crises such as food contamination fatalities and the sale of illegal medicines. This contrast underscores disparities in institutional capacity and sectoral prioritisation.Objectives: This paper investigated regulatory gaps and enforcement challenges in informal medicine markets, with a focus on spaza shops. The focus was on structural, operational, and social factors influencing the circulation of counterfeit, expired, and improperly stored medicines, and explores how governance, public service delivery, and community dynamics interact to affect public health outcomes.Methods: A qualitative case-study approach guided this research, focusing on the analysis of secondary data sources and qualitative literature. Purposive selection of documents and reports included government communications, regulatory guidelines, parliamentary hearing transcripts, media coverage, and peer-reviewed studies, ensuring that the sources provided rich insights into governance, regulatory enforcement, and informal pharmaceutical practices.Findings: Systemic gaps exist between regulatory intent and operational reality. Although legal frameworks restrict the dispensing of scheduled medicines to licensed pharmacies and authorised health professionals, widespread non-compliance persists in township spaza shops.Conclusion: Effective mitigation of counterfeit and illegally sold medicines requires an integrated, multi-dimensional approach that strengthens regulatory oversight, secures supply chains, mobilises community engagement, and leverages technological monitoring. The proposed Integrated Regulatory-Community Framework for Counterfeit Medicines in Spaza Shops (IRCF-CMSS) aligns formal legislation with practical enforcement and social realities, promoting sustained compliance, enhanced public safety, and institutional trust.